2018
DOI: 10.1038/s41598-018-19689-0
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Akt1 interactome and its role in regulating the cell cycle

Abstract: Cell growth and proliferation are two diverse processes yet always linked. Akt1, a serine/threonine kinase, is a multi-functional protein implicated in regulation of cell growth, survival and proliferation. Though it has a role in G1/S progression, the manner by which Akt1 controls cell cycle and blends cell growth with proliferation is not well explored. In this study, we characterize the Akt1 interactome as the cell cycle progresses from G0 to G1/S and G2 phase. For this, Akt1-overexpressing HEK293 cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 43 publications
2
13
1
Order By: Relevance
“…A possible mechanism is that nicotine activates RAS/MAPK pathway via nicotinic acetylcholine receptors (nAChRs) to trigger a network that positively regulates cell-cycle progression through G1 to S, such as cyclin D (Hong et al., 2017). Here, although no expression difference was observed on cyclin D and RAS/MAPK in our scRNA-seq data, we found that the components of cell-cycle machinery, such as HSP90AA1 , TUBB4B , and TUBA1B , which are related to G2M transition (Duggal et al., 2018), and HNRNPH1 and HNRNPA2B1 , which are related to G1 to S transition (Duggal et al., 2018), are upregulated in nicotine-exposed muscle cell cluster 3.…”
Section: Discussioncontrasting
confidence: 62%
“…A possible mechanism is that nicotine activates RAS/MAPK pathway via nicotinic acetylcholine receptors (nAChRs) to trigger a network that positively regulates cell-cycle progression through G1 to S, such as cyclin D (Hong et al., 2017). Here, although no expression difference was observed on cyclin D and RAS/MAPK in our scRNA-seq data, we found that the components of cell-cycle machinery, such as HSP90AA1 , TUBB4B , and TUBA1B , which are related to G2M transition (Duggal et al., 2018), and HNRNPH1 and HNRNPA2B1 , which are related to G1 to S transition (Duggal et al., 2018), are upregulated in nicotine-exposed muscle cell cluster 3.…”
Section: Discussioncontrasting
confidence: 62%
“…Futhermore, the PPI network showed that CDK1, HSP90AA1, AKT1, BCL2L1, HDAC2, HELLS, and KIF23 are 7 central genes identified by the top 10 high hub nodes after gene overlap. Among these central genes, CDK1 is a set of Ser/Thr kinase system corresponding to cell cycle progression ( 35 ), and its differential expression was found in another vitiligo study ( 36 ); HSP90AA1 plays a key role in signal transduction, protein folding, protein degradation, and morphological evolution ( 37 ); AKT1 and BCL2L1 are involved in apoptosis ( 38 , 39 ), and AKT methylation has been shown to promote skin tumors ( 40 ); HDAC2 interferes with histone deacetylase function ( 41 ); KIF23 plays an important role in the changes of cellular motor cytoskeleton ( 42 ); HELLS is considered to be a regulator of cell senescence and is necessary for DNMT1-mediated methylation maintenance and DNMT3A/DNMT3B-mediated remethylation ( 43 ). Therefore, we speculate that these hub genes may be involved in the pathological process in the early stage of melanocyte loss in vitiligo, but further functional experiments are needed to further explore.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of the intracellular Ca 2+ ions activate phosphatase such as pleckstrin homology domain leucine-rich repeat protein phosphatase PHLPP that specifically dephosphorylate AKT-1 on Ser473 and with less extended protein phosphatases PP2A that may also dephosphorylate AKT-1 at Ser473 [ 57 ]. The cytosolic AKT-1 dephosphorylation is per se responsible for G2 phases accumulation [ 58 ]. The nuclear AKT-1 dephosphorylation can be responsible for G1 phases accumulation induced by PAX following interaction with the nuclear membrane BK channel and a reduction of the nuclear membrane area as observed in our experiments.…”
Section: Discussionmentioning
confidence: 99%